2017
DOI: 10.1021/acs.orglett.7b01170
|View full text |Cite
|
Sign up to set email alerts
|

Inherently Chiral Upper-Rim-Bridged Calix[4]arenes Possessing a Seven Membered Ring

Abstract: The mercuration of calix[4]arene immobilized in the cone conformation allowed the introduction of an amino group at the meta position of the basic skeleton. Acylation and subsequent intramolecular Bischler-Napieralski-type cyclization led to a novel type of bridged calixarene containing a seven-membered ring. These compounds with an enlarged and rigidified cavity represent a unique and inherently chiral system that may potentially be applicable for the design of chiral receptors. The absolute configuration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…4 ‐{ N ′‐[3,5‐Bis(trifluoromethyl)phenyl]ureido}‐25,26,27,28‐tetrapropoxycalix[4]arene ( 6 ). 4‐Amino‐25,26,27,28‐tetrapropoxycalix[4]arene (0.2 g, 0.32 mmol) was stirred at room temperature in dichloromethane (10 mL) under nitrogen atmosphere. 3,5‐Bis(trifluoromethyl)phenyl isocyanate (0.148 g, 0.1 mL, 0.58 mmol) was added, and the mixture was stirred overnight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 ‐{ N ′‐[3,5‐Bis(trifluoromethyl)phenyl]ureido}‐25,26,27,28‐tetrapropoxycalix[4]arene ( 6 ). 4‐Amino‐25,26,27,28‐tetrapropoxycalix[4]arene (0.2 g, 0.32 mmol) was stirred at room temperature in dichloromethane (10 mL) under nitrogen atmosphere. 3,5‐Bis(trifluoromethyl)phenyl isocyanate (0.148 g, 0.1 mL, 0.58 mmol) was added, and the mixture was stirred overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Yield 0. 25 18 (0.2 g, 0.32 mmol) was stirred at room temperature in dichloromethane (10 mL) under nitrogen atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…Both involve unusual chemistry to directly install meta ‐functionality without resorting to directing groups, although to date neither has demonstrated an asymmetric version of their method. Lhoták's organomercurial route is arguably better in terms of yield and scope, and allows for the direct incorporation of mercury chloride into the meta ‐position of a calixarene . Whilst the toxicity issues of mercury cannot be ignored, the versatility of this reaction is extremely rich, giving meta ‐functionalised calix[4]arenes that are almost impossible to access by any other method (Scheme ).…”
Section: Meta‐functionalisationmentioning
confidence: 99%
“…Whilst the toxicity issues of mercury cannot be ignored, the versatility of this reaction is extremely rich, giving meta ‐functionalised calix[4]arenes that are almost impossible to access by any other method (Scheme ). The mono‐ meta ‐mercurial derivative was available in the best yields (60 %), and could be readily transformed into a number of extremely versatile groups as shown in Scheme . The authors have suggested that the unusual selectivity for the meta ‐position is due to favourable cation–π interactions between the mercury(II) atom and a neighbouring aryl ring noted in the crystal structure they obtained .…”
Section: Meta‐functionalisationmentioning
confidence: 99%
“…Furthermore, we show that ( R , S p * )‐ H 2 4 and ( R , R p * )‐ H 2 5 have different affinities for chiral viologen guest molecules. (for recent other chiral cage compounds, see refs …”
Section: Introductionmentioning
confidence: 99%